The return of metabolism: biochemistry and physiology of the pentose phosphate pathway. (22nd September 2014) - Stincone, Anna; Prigione, Alessandro; Cramer, Thorsten; Wamelink, Mirjam M. C.; Campbell, Kate; Cheung, Eric; Olin‐Sandoval, Viridiana; Grüning, Nana‐Maria; Krüger, Antje; Tauqeer Alam, Mohammad; Keller, Markus A.; Breitenbach, Michael; et al.
ABSTRACT The pentose phosphate pathway (PPP) is a fundamental component of cellular metabolism. The PPP is important to maintain carbon homoeostasis, to provide precursors for nucleotide and amino acid biosynthesis, to provide reducing molecules for anabolism, and to defeat oxidative stress. The PPP shares reactions with the Entner–Doudoroff pathway and Calvin cycle and divides into an oxidative and non‐oxidative branch. The oxidative branch is highly active in most eukaryotes and converts glucose 6‐phosphate into carbon dioxide, ribulose 5‐phosphate and NADPH. The latter function is critical to maintain redox balance under stress situations, when cells proliferate rapidly, in ageing, and for the 'Warburg effect' of cancer cells. The non‐oxidative branch instead is virtually ubiquitous, and metabolizes the glycolytic intermediates fructose 6‐phosphate and glyceraldehyde 3‐phosphate as well as sedoheptulose sugars, yielding ribose 5‐phosphate for the synthesis of nucleic acids and sugar phosphate precursors for the synthesis of amino acids. Whereas the oxidative PPP is considered unidirectional, the non‐oxidative branch can supply glycolysis with intermediates derived from ribose 5‐phosphate and vice versa, depending on the biochemical demand. These functions require dynamic regulation of the PPP pathway that is achieved through hierarchical interactions between transcriptome, proteome and metabolome. Consequently, the biochemistry and regulation of this pathway, while still unresolved in many cases, are archetypal for the dynamics of the metabolic network of the cell. In this comprehensive article we review seminal work that led to the discovery and description of the pathway that date back now for 80 years, and address recent results about genetic and metabolic mechanisms that regulate its activity. These biochemical principles are discussed in the context of PPP deficiencies causing metabolic disease and the role of this pathway in biotechnology, bacterial and parasite infections, neurons, stem cell potency and cancer metabolism.